Case Report: Low Bone and Normal Lean Mass in Adolescents With Complete Androgen Insensitivity Syndrome - Misakian, Aaron; McLoughlin, Michelle; Pyle, Louisa C.; Kolon, Thomas F.; Kelly, Andrea; Vogiatzi, Maria G. (Frontiers in Endocrinology, 2021)
Introduction: Osteopenia and osteoporosis have been reported in adults with Complete Androgen Insensitivity Syndrome (CAIS). Little is known about changes in bone mineral density (BMD) in adolescents with CAIS and whether it is affected by early gonadectomy. Body composition data have not been reported. Methods: Single center, retrospective study of CAIS adolescents who underwent dual-energy x-ray absorptiometry (DXA) (Hologic, Horizon A). Body composition is presented as lean body and fat mass indices (LMI, FMI). Z-scores for lumbar spine areal BMD (LBMD), total body less head (TBLH) bone mineral content (BMC), LMI and FMI were calculated using female normative data. Results are expressed as median and min,max. Results: Six females with genetically confirmed CAIS were identified – 1 with intact gonads and 5 with history of gonadectomy at 2-11 months. In the subject with intact gonads LBMD-Z and TBLH BMC-Z were -1.56 and -1.26 respectively at age 16 years. Among those with gonadectomy, LBMD-Z was -1.8 (-3.59 to 0.49) at age 15.6 years (12-16.8) and decreased in all 3 subjects who had longitudinal follow-up despite hormone replacement therapy (HRT). Adherence to HRT was intermittent. LMI Z and FMI Z were 0.1 (-1.39 to 0.7) and 1.0 (0.22 to 1.49) respectively. Conclusions: These limited data indicate that adolescents with CAIS have bone mass deficit. Further studies are needed to understand the extent of BMD abnormalities, the effect of gonadectomy, especially early in childhood, and to establish the optimal HRT regimen for bone accrual. Data on lean mass are reassuring.